Influencia da maturacao sexual no limiar de lactato em jogadoras de futebol - Nicolao, A. L. A.; Pedrinelli, A.; Zogaib, P. S. M.; Orbetelli, R.; Barros Neto, T. L. de (Revista Brasileira de Medicina do Esporte, 2010)
The lactate thresholds are used to assess the aerobic capacity in different ages. Studies show that children and adolescents present less lactate blood concentrations [La] than adults under certain effort loads. There are evidences that this is related to their maturational development. OBJECTIVE: To verify the association between the sexual maturation and the lactate threshold in some adolescent soccer players ranging from 12 to 15 years old. METHOD: The sample was related to the intentional and not probabilistic type involving 36 girls, from 12 to 15 years old, members of the soccer schools held by the Mayority of São Paulo. The body weight, height and the sum of two skinfolds - calf and triceps were obtained from the sample. A physician directly observed the sexual maturation of the genitals and pubic hair development through the Tanner index.To determine the lactate threshold a progressive test, a 3x800m in running track, was performed by adolescents, their effort intensity was controlled by pre-established heart rate zones and the lactate blood concentrations [La] were measured at the end of each run. The velocity corresponding to lactate blood concentrations [La] of 2,5mmol (V2,5) was obtained through the linear interpolation.The multiple linear regression was used to better understand the nature of these associations between the variables, considering the lactate threshold (V2,5) as a dependent variable and the age (years), the body weight index (kg/m2), height (cm) and the sum of the skinfolds (mm) as independent variables. RESULT: The growth variables and the sexual maturation have little association with the lactate threshold in the youngest and pre-adolescent girls. It is important to take in consideration the sexual maturation influence on the threshold lactate. CONCLUSION: Taking in account the group homogeneity and being the range between 12 and 15 years old a period susceptible to many modifications, the maturational development and not the chronological age showed to be reponsible for a significative difference in the analysed variables.